2017
DOI: 10.29356/jmcs.v56i2.310
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of the Behaviors of the Bray-Liebhafsky Oscillating Chemical Reaction by a Four-variable Model

Abstract: Based on a ten-step chemical model involving the concentrations of I<sub>2</sub>(aq), O<sub>2</sub>(aq), and the intermediates of I<sup>-</sup> and HIO<sub>2</sub>, four independent variables and seven irreversible steps, the nonlinear behavior of Bray-Liebhafsky (BL) oscillating reaction was investigated. The results showed that with different values of initial concentrations of reactants in the process of simulation, both periodic oscillation and chaotic behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…When the RGY model was first presented it was suggested that the system might be chaotic. It was argued that chaos is present due to the existence of large positive Lyapunov exponents [14]. (A Lyapunov exponent is a quantitative measurement of a dynamical system which characterizes the rate at which nearby trajectories converge or diverge asymptotically.…”
Section: (A) Dynamics and Chaosmentioning
confidence: 99%
See 4 more Smart Citations
“…When the RGY model was first presented it was suggested that the system might be chaotic. It was argued that chaos is present due to the existence of large positive Lyapunov exponents [14]. (A Lyapunov exponent is a quantitative measurement of a dynamical system which characterizes the rate at which nearby trajectories converge or diverge asymptotically.…”
Section: (A) Dynamics and Chaosmentioning
confidence: 99%
“…Various candidate reaction mechanisms have been proposed and these include those by Treindl & Noyes [11] and Schmitz [12,13]. Ren et al [14,15] developed a new mechanism by reducing a set of equations originally proposed by Kolar-Anić et al [16] and modified by Kissimonová et al [17] by ignoring the reversibility of some steps. This led to the set of ten chemical equations given by…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations